PROGRAM PENGUATAN PEMBENTUKAN KARAKTER SISWA MELALUI GERAKAN 5S (SENYUM, SALAM, SAPA, SOPAN, SANTUN) DAN PEMBIASAAN POSITIF DI SMPN 7 CIRACAP SATU ATAP - Eni nuraeni Nuraeni; Asep Sahrul Gunawan; Siti Nursidah; Rahela Sopia Nupus; Risa Ryani; Riki Ruswandi; Siti Fauzia Rahma; Ripal; Bella Sindy Putri (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
One of the Tri Dharma of Higher Educa tion is to make a tangible contribution to society, particularly in the field of education, through community service activities. Since education focuses not only on improving academic abilities but also on fostering positive attitudes and behaviors, character education is a crucial component in the process of shaping students. With the rapid development of technology and social changes, the character development of students faces challenges such as a loss of discipline, social awareness, responsibility, and interpersonal ethics. This community service activity was carried out at SMPN 7 Ciracap Satu Atap with the aim of strengthening students’ character development through the implementation of the 5S Movement (Smile, Greeting, Hello, Politeness, Courtesy) and fostering positive habits within the school environment. The program was implemented as a form of support for the habit-forming activities already in place at the school, such as the flag ceremony, congregational Duha and Dhuhr prayers, morning exercises, community service, classroom duty, Student Council (OSIS) activities, Student Representative Council (MPK) activities, Scouting, and other religious activities. The results showed that students were highly engaged in the program. In addition, students gained a better understanding of the importance of practicing discipline, responsibility, cooperation, social awareness, and good manners in their daily lives. It is hoped that this program will serve as one of the efforts to strengthen character education on an ongoing basis